Biodiversity Information System: Tropical Rainforest Borneo and Traditional Knowledge Ethnic of Dayak - Dengen, Nataniel; Budiman, Edy; Widians, Joan Angelina; Wati, Masna; Hairah, Ummul; Ugiarto, Muhammad (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Although it has become an important theme, and it is mainstreaming in national development planning system, biodiversity is still not seen as a matter of urgency. The biodiversity data of existing plants in Kalimantan is still separated and scattered in various government and private research institutions; it has not been collected in a database management system. This research is an advanced research and development of plant biodiversity information system. To date, the collections of data include 1.497 species of trees, 276 species of wood, and 233 species of medicinal plants based on traditional knowledge of 45 sub-ethnic of Dayak. Efforts to accelerate research and development of biodiversity on Borneo island needs to be driven at high speed, given the environmental changes that occur at present; we are in a race with deforestation and forest degradation. Many potentials plant species that hurried-extinct before it is discovered, only because we pursue economic growth that converts areas of tropical rainforest into oil palm plantations, agricultural land, and other plantations.